Lignin janus hydrogel patch as well as preparation method and application thereof

By pre-stretching and hydroxylation treatment on the base layer of the hydrogel patch and forming a lignin-based hydrogel with both adhesion and anti-adhesion properties on its surface, the problem of double-sided adhesion in internal wound repair is solved, and the antibacterial, anti-inflammatory and mechanical shrinkage effects are achieved, which significantly accelerates the wound healing process.

CN119770698APending Publication Date: 2025-04-08XIEHE HOSPITAL ATTACHED TO TONGJI MEDICAL COLLEGE HUAZHONG SCI & TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411816564.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing hydrogels have a problem of double-sided adhesion in internal wound repair, which cannot effectively prevent bacterial infection and tissue inflammatory response, and at the same time lack mechanical contraction forces to accelerate wound healing.

Method used

A lignin-janus hydrogel patch was developed. By pre-stretching and hydroxylation treatment on the base layer, and forming a lignin-based hydrogel with both adhesion and anti-adhesion properties on its surface, using photo-induced radical polymerization technology to prepare a hydrogel patch with antibacterial, anti-inflammatory and mechanical shrinkage capabilities.

Benefits of technology

It provides antibacterial, anti-inflammatory and excellent tissue adhesion in the wound area, while preventing external pollutants from contaminating the wound surface. It can initiate mechanical self-contraction after contacting the wet tissue of the wound, effectively accelerating wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770698A_ABST
    Figure CN119770698A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological medicines, and particularly discloses a lignin janus hydrogel patch as well as a preparation method and application thereof. The lignin janus hydrogel patch comprises a substrate layer and a tissue adhesion layer, wherein the substrate layer is pre-stretched, one surface of the substrate layer is subjected to hydroxylation treatment, and the tissue adhesion layer is attached to the hydroxylated surface of the substrate layer through lignin-based hydrogel and is subjected to photo-initiated free radical polymerization; the invention also discloses an application of the lignin janus hydrogel patch in preparation of a patch for promoting soft tissue defect or wound healing. In the lignin janus hydrogel patch disclosed by the invention, the lignin janus hydrogel patch has different adhesion properties, and the adhesion surface has excellent adhesion property, mechanical property and antibacterial property; after contacting with wet tissue of a wound, a strain program can be started to perform mechanical self-constriction, thereby effectively helping the wound to be closed and accelerating the repairing speed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedicine, and in particular relates to a lignin janus hydrogel patch and a preparation method and application thereof. Background Art

[0002] At present, surgical sutures are usually used clinically to connect wound tissues together for the treatment of soft tissue defects or injuries, especially for internal wounds. However, surgical sutures still have some obvious defects, such as secondary bleeding during suturing, postoperative infection, normal tissue damage, etc. With the continuous development of biomedical materials, bioadhesives such as peptides, fibrin glue, and hydrogels have been reported one after another, which have great advantages over traditional surgical sutures. Among them, hydrogels, as a soft material close to biological tissues, have shown great advantages in the field of wound repair due to their unique controllable physical and chemical properties and mechanical properties and excellent biocompatibility. Compared with skin wound healing, due to the extremely complex environment in the body, it is more challenging to develop a new integrated hydrogel that can prevent bacterial infection, reduce tissue inflammatory response, and promote internal soft tissue wound repair.

[0003] In the continuous and dynamic in vivo environment, especially in the abdomen and chest, the contact between wet tissue surfaces and different organs is the biggest challenge for internal wound repair, which requires hydrogels to have not only strong adhesion to wet tissue defects, but also anti-adhesion to other normal tissues. However, most of the hydrogels reported in the past only focused on improving tissue adhesion strength, showing indiscriminate double-sided adhesion. In addition, in the face of wound repair and remodeling, mechanical force regulation of wounds to induce wound contraction to accelerate wound healing has become a promising wound healing strategy. Therefore, the ideal hydrogel often needs to have good biocompatibility, antibacterial, anti-inflammatory, anti-fouling and adhesion properties to different tissues while providing a certain mechanical contraction force to the wound tissue, thereby accelerating wound closure.

[0004] Lignin, as the most abundant renewable polyphenol compound in nature, is non-toxic, antioxidant, antibacterial, biodegradable, and biocompatible. Introducing it into the design and preparation of new hydrogels for wound repair will have great application potential. Therefore, the development of lignin janus hydrogels that have antibacterial, anti-inflammatory, adhesive and anti-adhesive properties, while providing mechanical contraction for wound tissue, is an effective way to solve the above problems and has far-reaching significance. Summary of the invention

[0005] In view of the above problems, the present invention provides a lignin janus hydrogel patch and a preparation method and application thereof, mainly to solve the problem that the current wound dressing cannot be comprehensively developed in terms of antibacterial, anti-inflammatory, adhesion and anti-adhesion properties, and also solves the problem that there is currently no effective method to prepare the aforementioned patch.

[0006] In order to solve the above problems, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention relates to a lignin janus hydrogel patch, comprising a base layer and a tissue adhesion layer; wherein the base layer is pre-stretched and one side thereof is hydroxylated, the tissue adhesion layer is formed by attaching a lignin-based hydrogel to the hydroxylated side of the base layer and undergoing photo-initiated free radical polymerization to obtain a lignin janus hydrogel having both an adhesion surface and an anti-adhesion surface, and the tissue adhesion layer is hydrogen-bonded to the hydroxylated surface. The tissue adhesion layer is generally solid in a standby state (but the present invention does not exclude non-solid state), and the base layer can be shaped. When the tissue adhesion layer encounters moisture from a wound during use, the tissue adhesion layer becomes soft, and the base layer can shrink to stretch the wound. That is, janus hydrogel refers to a hydrogel having two opposite properties, one side having adhesiveness and the other side having no adhesiveness, and the tissue adhesion layer being a flexible hydrogel or air-dried and hardened should all be within the scope of the present invention.

[0008] As for the lignin janus hydrogel patch, its properties can be specifically defined as follows, any one of which can be independently selected for reference:

[0009] Wherein, the base layer is at least any one of a biological material, a composite material, and a polymer synthetic material; preferably, the base layer is a silicone base layer, and further, the silicone can shrink after being stretched.

[0010] Among them, the other side of the base layer is fluorinated, and the fluorination treatment can make this side more hydrophobic. The hydrophobic property after fluorination can prevent biological contamination (bacteria, feces, etc.) on the surface of the patch, prevent adhesion between tissues, and help the shrinkage of rubber.

[0011] Among them, the lignin janus hydrogel on the rubber surface is generally solid after air drying (other similar means are equivalent), which can shape the pre-stretched rubber. The rubber will shrink after stretching, and this shrinkage property is used to shrink the wound in clinical applications. Specifically, when the rubber is stretched, the gel is coated on its surface. When the hydrogel dries, it can shape the pre-stretched rubber to prevent the rubber from shrinking. When the hydrogel encounters the moisture of the wound, it becomes soft as a whole, and the rubber can shrink.

[0012] The tissue adhesion layer is formed by coating a tissue adhesion liquid on a hydroxylated side of a substrate layer and polymerizing it through photoinitiated free radicals; the tissue adhesion liquid is formed by mixing a lignin / metal ion mixture and a gelatin / monomer mixture and adding at least one of acetone, β-keto acid, oxaloacetic acid, α-glutaric acid, phenylpropiotone or cyclohexanone. The monomer is one or more of acrylic acid, acrylic acid and polyvinyl alcohol. Furthermore, the lignin / metal ion mixture is obtained by mixing ammonia water and a metal salt solution and adding a lignin solution; the lignin / metal ion mixture mainly utilizes the reaction of lignin with a metal salt solution to form a lignin / metal ion redox system, and then a one-pot method can be used to synthesize a lignin-based hydrogel with antibacterial, anti-inflammatory and excellent mechanical properties with the gelatin / monomer mixture.

[0013] Wherein, the lignin / metal ion mixture and the gelatin / monomer mixture are obtained by the following methods respectively: lignin / metal ion mixture: ammonia water is added dropwise to the metal salt solution, stirred to obtain a metal ion salt ammonia solution, and then the lignin solution is added, stirred and allowed to stand; gelatin / monomer mixture: gelatin is added to deionized water, stirred and dissolved at 40°C to 60°C, and then the monomer is added, and the monomer is one or more of acrylic acid, acrylic acid, and polyvinyl alcohol. Furthermore, in the preparation of the lignin mixture: the metal salt solution is any one of copper nitrate, aluminum nitrate, silver nitrate, zinc nitrate, and iron nitrate, and preferably, the concentration of the metal salt solution is 0.5mg / mL to 5.5mg / mL; the lignin is an alkali lignin with a molecular weight of 500 to 10000 or a sodium lignin sulfonate with a molecular weight of 100 to 8000, and preferably, the concentration of the lignin solution is 0.1mol / L to 0.4mol / L.

[0014] The second aspect of the present invention relates to a method for preparing a lignin janus hydrogel patch, comprising the following steps:

[0015] Preparation of the base layer: one side of the silica gel sheet is hydroxylated to obtain a modified base layer;

[0016] Preparation of tissue adhesion layer solution: mixing ammonia water and aluminum nitrate solution, adding sodium lignin sulfonate to obtain a lignin aluminum / ammonia water mixed solution, mixing a monomer / gelatin mixed solution with a lignin aluminum / ammonia water mixed solution, and adding at least one of acetone, β-keto acid, oxaloacetic acid, α-glutaric acid, phenylpropiotone or cyclohexanone to obtain a tissue adhesion layer solution, wherein the monomer is one or more of acrylic acid, acrylic acid, and polyvinyl alcohol;

[0017] Preparation of lignin janus hydrogel patch: stretching the modified base layer, coating the tissue adhesion layer solution on the hydroxylated surface of the modified base layer, and irradiating with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the base layer.

[0018] As for the preparation method of the lignin janus hydrogel patch, its properties can be specifically defined as follows, any one of which can be independently selected for reference:

[0019] Wherein, the base layer is any one of a biological material, a composite material, and a polymer synthetic material, preferably silicone. Furthermore, the silicone can shrink after being stretched.

[0020] Wherein, the other side of the base layer is fluorinated; preferably, the fluorinating agent is added dropwise and air-dried to fluorinate the silicone sheet, and more preferably, the fluorinating agent is any one of trichloro(3,3,3-trifluoropropyl)silane, perfluorodecyltriethoxysilane and trimethoxy(3,3,3-trifluoropropyl)silane.

[0021] The lignin aluminum / ammonia water mixed solution and the acrylic acid / gelatin mixed solution can be mixed in a ratio of 1:100 to 1:20.

[0022] Among them, after applying the tissue adhesion layer solution, it is air-dried. The air-dried hydrogel can prevent the silicone from shrinking randomly, ensuring that the hydrogel on the rubber surface becomes soft as a whole after encountering the moisture of the wound, and the rubber shrinks at this time.

[0023] The present invention utilizes lignin and a metal salt solution to form a lignin / metal ion redox system, adopts a one-pot method to synthesize a lignin-based hydrogel with antibacterial, anti-inflammatory and excellent mechanical properties, and uniformly coats the system on the surface of a pre-stretched silicone rubber that has been activated. Free radical polymerization is then initiated by ultraviolet light to obtain a lignin janus hydrogel with both an adhesive surface and an anti-adhesive surface. The system solves the problems of double-sided adhesion performance, insufficient mechanical properties, weak adhesion performance and no antibacterial performance of traditional hydrogels, and broadens the application of hydrogels in the biomedical field.

[0024] The third aspect of the present invention relates to the use of the aforementioned lignin janus hydrogel patch in the preparation of a patch for promoting the healing of soft tissue defects or injuries. The combination of the strain-programmed self-shrinking patch and the lignin gel produces a synergistic effect to promote wound healing, especially promoting the healing of soft tissue defects or injuries.

[0025] As for the application of lignin janus hydrogel patch, its properties can be specifically defined as follows, any one of which can be independently selected for reference:

[0026] The patch for promoting healing of soft tissue defects or injuries can initiate a strain program to perform mechanical self-contraction after contacting the wet tissue of the wound. Specifically, when the tissue adhesion layer contacts the wet tissue of the wound, the hydrogel softens so that the silicone can contract.

[0027] Wherein, the soft tissue is visceral soft tissue or intestinal tissue. The patch that promotes the healing of soft tissue defects or injuries can be used to repair wounds in the abdomen, chest or between different organs that are in contact with each other. It can have strong adhesion to wet tissue defects and can also have anti-adhesion to other normal tissues. For example, in clinical practice, intestinal wounds may be caused by surgery-related factors, systemic factors, local factors, nursing factors, trauma or pressure injuries, inflammatory diseases and infections. This product can be used in any case where there is a wound in the intestine. For example, it can be used to repair wounds of visceral soft tissues such as the heart, liver, spleen, lungs, and kidneys. Other wounds on the surface of the internal organs can also be directly fitted with this product. The silicone sheet will eventually remain in the body. The silicone can remain in the body safely under the premise of being qualified. Specifically, intestinal wounds are mainly infected intestinal wounds.

[0028] Based on the adhesion properties and strain programming of the lignin janus hydrogel patch, the adhesive surface of the lignin janus hydrogel patch can provide excellent antibacterial, anti-inflammatory and tissue adhesion effects at the wound site, and the anti-adhesion surface can prevent external pollutants from contaminating the wound surface. At the same time, the patch can activate the strain program to perform mechanical self-contraction after contacting the wet tissue of the wound, effectively helping the wound to close, and ultimately achieving multi-faceted promotion of wound healing and tissue repair.

[0029] In the present disclosure, the lignin janus hydrogel patch forms a lignin / metal ion redox system by utilizing lignin and a metal salt solution, and performs photo-initiated free radical polymerization on a rubber surface that has been surface activated and pre-stretched. The preparation method is simple, the conditions are mild, the preparation is easy, and it is convenient for large-scale production. The lignin janus hydrogel patch has different adhesion properties. The adhesion surface has excellent adhesion properties, mechanical properties, and antibacterial properties, which effectively promote wound healing. The anti-adhesion surface can prevent the wound from being contaminated by dirt and prevent adhesion to surrounding normal tissues. The lignin janus hydrogel patch can initiate a strain program to perform mechanical self-contraction after contacting the wet tissue of the wound, which effectively helps the wound to close and accelerates the repair speed. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a graph showing the test results of the hydrophobic properties of the silicone rubber layer of the lignin Janus hydrogel patch.

[0031] Figure 2 These are actual photos of the adhesion performance test between the tissue adhesion layer of the lignin janus hydrogel patch and the surfaces of different materials.

[0032] Figure 3 This is a graph showing the adhesion performance test results of the base layer and tissue adhesion layer of the lignin janus hydrogel patch.

[0033] Figure 4 This is the tensile properties test result of lignin janus hydrogel patch.

[0034] Figure 5 This is a test result of the lignin janus hydrogel patch in promoting intestinal wound healing.

[0035] Figure 6 This is a diagram showing the results of histopathological analysis of the strain-programmed lignin janus hydrogel patch prepared by the present invention in promoting intestinal wound healing. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific research examples.

[0037] Example section

[0038] Embodiment 1:

[0039] 1. Preparation of base layer:

[0040] (a) During the molding process of the silicone rubber sheet, trichloro(3,3,3-trifluoropropyl)silane is added dropwise for fluorination treatment, and the sheet is air-dried to obtain a single-sided fluorinated silicone rubber sheet.

[0041] (b) The other side of the silicone rubber is treated with a plasma surface treatment machine ( H arr i c kPl asma ) for hydroxylation treatment, place the nozzle of the plasma surface treatment machine vertically above the silicone surface, and continue to treat the silicone surface for 2 minutes.

[0042] 2. Preparation of tissue adhesion layer solution:

[0043] (a) 0.1 mL of aqueous ammonia was added dropwise to 5 mL of 3 mg / mL aluminum nitrate solution, and the mixture was stirred thoroughly to obtain an aluminum nitrate / ammonia solution; subsequently, 3 mL of 0.2 mol / L sodium lignin sulfonate aqueous solution was added, the mixture was stirred for 1 hour, and the mixture was allowed to stand for 3 hours to obtain an aluminum lignin / ammonia solution.

[0044] (b) 0.2 g of gelatin was dissolved in 10 mL of deionized water, and the mixture was stirred at 50° C. until dissolved. 2 g of acrylic acid was added to obtain an acrylic acid / gelatin mixed solution.

[0045] (c) The lignin aluminum / ammonia water mixed solution and the acrylic acid / gelatin mixed solution were mixed at a volume ratio of 1:50. After the mixture was evenly mixed, 0.01 g of acetone was added and the mixture was stirred thoroughly to obtain a tissue adhesion layer solution.

[0046] 3. Preparation of the lignin janus hydrogel patch:

[0047] (a) The double-sided substrate layer with different modifications is stretched.

[0048] (b) The tissue adhesion layer solution is evenly coated on one side of the basal layer that has been stretched and hydroxylated, and then irradiated with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the basal layer, and finally air-dried to obtain a lignin janus hydrogel patch with both a tissue adhesion surface and an anti-adhesion surface. The mechanical properties and adhesion properties of the lignin janus hydrogel patch are shown in Table 1.

[0049] Embodiment 2:

[0050] 1. Preparation of base layer:

[0051] (a) Trimethoxy(3,3,3-trifluoropropyl)silane was added dropwise to one side of a silicone rubber sheet for fluorination treatment, and then air-dried to obtain a single-sided fluorinated silicone rubber sheet.

[0052] (b) The other side of the silicone rubber is hydroxylated using a plasma surface treatment machine.

[0053] 2. Preparation of tissue adhesion layer solution:

[0054] (a) 0.2 mL of aqueous ammonia was added dropwise to 6 mL of a 5 mg / mL copper nitrate solution, and the mixture was stirred thoroughly to obtain a copper nitrate / ammonia solution. Subsequently, 2 mL of an alkaline lignin solution with a concentration of 0.2 mol / L was added, the mixture was stirred for 1 hour, and the mixture was allowed to stand for 1 hour to obtain a lignin copper / ammonia solution.

[0055] (b) 0.3 g of gelatin was dissolved in 10 mL of deionized water, and the mixture was stirred at 60° C. until dissolved. 2 mL of acrylic acid was added to obtain an acrylic acid / gelatin mixed solution.

[0056] (c) The lignin silver / ammonia water mixed solution and the acrylic acid / gelatin mixed solution were mixed at a volume ratio of 1:80. After the mixture was evenly mixed, 0.05 g of phenylacetone was added and the mixture was stirred thoroughly to obtain a tissue adhesion layer solution.

[0057] 3. Preparation of the lignin janus hydrogel patch:

[0058] (a) The double-sided substrate layer with different modifications is stretched.

[0059] (b) The tissue adhesion layer solution is evenly coated on one side of the basal layer that has been stretched and hydroxylated, and then irradiated with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the basal layer, and finally air-dried to obtain a lignin janus hydrogel patch with both a tissue adhesion surface and an anti-adhesion surface. The mechanical properties and adhesion properties of the lignin janus hydrogel patch are shown in Table 1.

[0060] Embodiment 3:

[0061] 1. Preparation of base layer:

[0062] (a) Trimethoxy(3,3,3-trifluoropropyl)silane was added dropwise to one side of a silicone rubber sheet for fluorination treatment, and then air-dried to obtain a single-sided fluorinated silicone rubber sheet.

[0063] (b) The other side of the silicone rubber is hydroxylated using a plasma surface treatment machine.

[0064] 2. Preparation of tissue adhesion layer solution:

[0065] (a) 0.1 mL of aqueous ammonia was added dropwise to 6 mL of a 5 mg / mL silver nitrate solution, and the mixture was stirred thoroughly to obtain a silver nitrate / ammonia solution; subsequently, 3 mL of a 0.2 mol / L sodium lignin sulfonate aqueous solution was added, the mixture was stirred for 1 hour, and the mixture was allowed to stand for 2 hours to obtain a lignin silver / ammonia solution.

[0066] (b) 0.3 g of gelatin was dissolved in 10 mL of deionized water, and the mixture was stirred at 60° C. until dissolved. 2 g of polyvinyl alcohol was added to obtain a polyvinyl alcohol / gelatin mixed solution.

[0067] (c) The lignin silver / ammonia water mixed solution and the polyvinyl alcohol / gelatin mixed solution were mixed at a volume ratio of 1:65. After the mixture was evenly mixed, 0.06 g of α-ketoglutaric acid was added and the mixture was stirred thoroughly to obtain a tissue adhesion layer solution.

[0068] 3. Preparation of the lignin janus hydrogel patch:

[0069] (a) The double-sided substrate layer with different modifications is stretched.

[0070] (b) The tissue adhesion layer solution is evenly coated on one side of the basal layer that has been stretched and hydroxylated, and then irradiated with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the basal layer, and finally air-dried to obtain a lignin janus hydrogel patch with both a tissue adhesion surface and an anti-adhesion surface. The mechanical properties and adhesion properties of the lignin janus hydrogel patch are shown in Table 1.

[0071] Embodiment 4:

[0072] 1. Preparation of base layer:

[0073] (a) Perfluorodecyltriethoxysilane was added dropwise to one side of a silicone rubber sheet for fluorination treatment, and then air-dried to obtain a single-sided fluorinated silicone rubber sheet.

[0074] (b) The other side of the silicone rubber is hydroxylated using a plasma surface treatment machine.

[0075] 2. Preparation of tissue adhesion layer solution:

[0076] (a) 0.5 mL of aqueous ammonia was added dropwise to 5 mL of a 5 mg / mL zinc nitrate solution, and the mixture was stirred thoroughly to obtain a zinc nitrate / ammonia solution; subsequently, 5 mL of an alkaline lignin solution with a concentration of 0.2 mol / L was added, the mixture was stirred for 1 hour, and the mixture was allowed to stand for 3 hours to obtain a lignin zinc / ammonia solution.

[0077] (b) 0.2 g of gelatin was dissolved in 10 mL of deionized water, and the mixture was stirred at 60° C. until dissolved. 2 mL of acrylic acid was added to obtain an acrylic acid / gelatin mixed solution.

[0078] (c) The lignin zinc / ammonia water mixed solution and the acrylic acid / gelatin mixed solution were mixed at a volume ratio of 1:100. After the mixture was evenly mixed, 0.01 g of β-keto acid was added and the mixture was stirred thoroughly to obtain a tissue adhesion layer solution.

[0079] 3. Preparation of the lignin janus hydrogel patch:

[0080] (a) The double-sided substrate layer with different modifications is stretched.

[0081] (b) The tissue adhesion layer solution is evenly coated on one side of the basal layer that has been stretched and hydroxylated, and then irradiated with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the basal layer, and finally air-dried to obtain a lignin janus hydrogel patch with both a tissue adhesion surface and an anti-adhesion surface. The mechanical properties and adhesion properties of the lignin janus hydrogel patch are shown in Table 1.

[0082] Embodiment 5:

[0083] 1. Preparation of base layer:

[0084] (a) Trimethoxy(3,3,3-trifluoropropyl)silane was added dropwise to one side of a silicone rubber sheet for fluorination treatment, and then air-dried to obtain a single-sided fluorinated silicone rubber sheet.

[0085] (b) The other side of the silicone rubber is hydroxylated using a plasma surface treatment machine.

[0086] 2. Preparation of tissue adhesion layer solution:

[0087] (a) 0.5 mL of aqueous ammonia was added dropwise to 5 mL of 5 mg / mL ferric nitrate solution, and the mixture was stirred thoroughly to obtain an ferric nitrate / ammonia solution. Subsequently, 5 mL of 0.2 mol / L sodium lignin sulfonate aqueous solution was added, the mixture was stirred for 1 hour, and the mixture was allowed to stand for 1 hour to obtain an ferric lignin / ammonia solution.

[0088] (b) 0.2 g of gelatin was dissolved in 10 mL of deionized water, and the mixture was stirred at 60° C. until dissolved. 2 g of acrylic acid was added to obtain an acrylic acid / gelatin mixed solution.

[0089] (c) The lignin iron / ammonia water mixed solution and the acrylic acid / gelatin mixed solution were mixed at a volume ratio of 1:60. After the mixture was evenly mixed, 0.06 g of oxaloacetic acid was added and the mixture was stirred thoroughly to obtain a tissue adhesion layer solution.

[0090] 3. Preparation of the lignin janus hydrogel patch:

[0091] (a) The double-sided substrate layer with different modifications is stretched.

[0092] (b) The tissue adhesion layer solution is evenly coated on one side of the basal layer that has been stretched and hydroxylated, and then irradiated with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the basal layer, and finally air-dried to obtain a lignin janus hydrogel patch with both a tissue adhesion surface and an anti-adhesion surface. The mechanical properties and adhesion properties of the lignin janus hydrogel patch are shown in Table 1.

[0093] Comparative Example 1:

[0094] The difference from Example 1 is that this comparative example does not perform ultraviolet irradiation initiation, and the other formulas and steps are the same as those in Example 1. The results of the prepared lignin hydrogel patch are shown in Table 1.

[0095] Comparative Example 2:

[0096] The difference from Example 1 is that no lignin metal salt solution is added in this comparative example, and other formulas and processes are the same as those in Example 1. The results of the prepared hydrogel are shown in Table 1.

[0097] Comparative Example 3:

[0098] The difference from Example 1 is that no catalyst is added in this comparative example, and the other formulas and steps are the same as those in Example 1. The results of the prepared lignin hydrogel are shown in Table 1.

[0099] Table 1: Performance test results of lignin janus hydrogel patch

[0100] Whether it is gel Tensile strength at break Adhesion strength Example 1 yes 213KPa 8.3KPa Example 2 yes 258KPa 5.7KPa Example 3 yes 323KPa 4.3KPa Example 4 yes 167KPa 5.6KPa Example 5 yes 328KPa 4.7KPa Comparative Example 1 no - - Comparative Example 2 yes 163KPa 0.5KPa Comparative Example 3 no - -

[0101] The above mechanical strength and adhesion strength were measured using a universal tensile testing machine (Shenzhen Sansi Experimental Equipment Co., Ltd.).

[0102] Hydrogel patch performance analysis part

[0103] Drop water on the fluorinated and non-fluorinated silicone rubber surfaces respectively, and analyze the contact angle between the water drop and the silicone rubber surface. Figure 1As shown in the figure, it was found that the fluorinated silicone rubber surface had a larger contact angle, indicating that the base layer of the fluorinated lignin janus hydrogel patch had excellent hydrophobic properties and anti-adhesion properties.

[0104] like Figure 2 As shown in , the adhesion properties of the tissue adhesion layer of the lignin janus hydrogel patch to the surfaces of different materials were tested, indicating that the tissue adhesion layer of the lignin janus hydrogel patch showed a strong adhesion effect to different materials, had excellent adhesion properties, and could effectively adhere to the wet tissue surface in the in vivo environment, especially to the surfaces of various organ tissues in the body.

[0105] like Figure 3 As shown in the figure, the adhesion properties of the basal layer and tissue adhesion layer of the lignin janus hydrogel patch were tested separately. The basal layer and tissue adhesion layer of the lignin janus hydrogel patch were adhered to the skin surface respectively. The experiment found that compared with the basal layer, the tissue adhesion layer can be firmly adhered to the skin surface, indicating that the two sides of the lignin janus hydrogel patch have different adhesion properties.

[0106] like Figure 4 As shown in , the tensile properties of the lignin janus hydrogel patch were tested. The lignin janus hydrogel patch and the hydrogel were subjected to tensile tests respectively. By analyzing the stress-strain curves of the lignin janus hydrogel patch and the hydrogel, it was shown that the lignin janus hydrogel patch had excellent mechanical properties, and the tensile resistance of the lignin janus hydrogel patch was significantly better than that of the hydrogel.

[0107] like Figure 5 As shown in , the ability of the strain-programmed lignin janus hydrogel patch to promote intestinal wound healing was tested. The experiment was divided into five groups, namely, blank group, PAA gel group, lignin silver gel group, strain-programmed janus patch (PAA gel group), and strain-programmed janus patch (lignin silver gel group). The lignin janus hydrogel patch and the hydrogel were tested on infected intestinal wounds respectively. By analyzing the healing of the wounds, it was shown that the strain-programmed lignin janus hydrogel patch had better performance than PAA gel, lignin Ag gel, etc. in promoting the healing of infected intestinal wounds, and the difference was significant. The ordinary patch is equivalent to the PAA gel patch, and its wound healing rate is much lower than that of the strain-programmed janus patch (lignin silver gel group).

[0108] like Figure 6As shown in the figure, pathological analysis of the tissues of the strain-programmed lignin janus hydrogel patch that promotes intestinal wound healing was performed. The experiment was divided into five groups, namely, the blank group, the PAA gel group, the lignin silver gel group, the strain-programmed janus patch (PAA gel group), and the strain-programmed janus patch (lignin silver gel group). Gram staining results showed that the strain-programmed self-contracting lignin janus hydrogel patch had the lowest bacterial content in the tissue after treatment. H&E staining results showed that the strain-programmed self-contracting lignin janus hydrogel patch had the best tissue healing effect and the lowest inflammatory response, confirming that the combined effect of the strain-programmed self-contracting patch and lignin gel can synergistically promote wound healing. Masson staining results showed that the content of new collagen in the tissue after treatment with the strain-programmed self-contracting lignin janus hydrogel patch was the highest. The statistical results of epithelial thickness, epithelial regeneration percentage, and collagen showed that the strain-programmed self-contracting lignin janus hydrogel patch had the best therapeutic effect, and the difference was significant. The wound healing rate of the ordinary patch, which was equivalent to the PAA gel patch, was much lower than that of the strain-programmed janus patch (lignin silver gel group).

[0109] It is clear to those skilled in the art that various modifications to the above embodiments can be made without departing from the overall spirit and concept of the present invention, and reference can be made to the prior art for any details not detailed herein. All of them fall within the scope of protection of the present invention. The protection scheme of the present invention shall be subject to the claims attached to the present invention.

Claims

1. Lignin janus hydrogel patch, characterized in that, Includes basal layer and tissue adhesion layer; The base layer is pre-stretched and one side thereof is hydroxylated, and the tissue adhesion layer is formed by lignin-based hydrogel attached to the hydroxylated side of the base layer and subjected to light-induced free radical polymerization.

2. The lignin janus hydrogel patch according to claim 1, characterized in that: The base layer is at least any one of a biological material, a composite material, and a polymer synthetic material; preferably, the base layer is a silicone base layer.

3. The lignin janus hydrogel patch according to claim 1, characterized in that: The other side of the base layer is fluorinated.

4. The lignin janus hydrogel patch according to claim 1, characterized in that: The tissue adhesion layer is formed by coating a tissue adhesion liquid on a hydroxylated side of the substrate layer and polymerizing the substrate through photoinitiated free radicals; The tissue adhesion liquid is prepared by mixing a lignin / metal ion mixed liquid and a gelatin / monomer mixed liquid and adding at least one of acetone, β-ketoacid, oxaloacetic acid, α-glutaric acid, phenylpropiotone or cyclohexanone to react; the lignin / metal ion mixed liquid is prepared by mixing ammonia water and a metal salt solution and adding a lignin solution to the mixture; the monomer is one or more of acrylic acid, acrylic acid and polyvinyl alcohol.

5. The lignin janus hydrogel patch according to claim 4, characterized in that: The lignin / metal ion mixed solution and the gelatin / monomer mixed solution are obtained by the following methods: Lignin / metal ion mixed solution: Ammonia water is added dropwise to the metal salt solution, stirred to obtain a metal ion salt ammonia solution, then the lignin solution is added, stirred and allowed to stand; Gelatin / monomer mixture: Add gelatin to deionized water, stir and dissolve at 40℃~60℃, then add monomer; Preferably, the lignin aluminum / ammonia water mixed solution and the acrylic acid / gelatin mixed solution can be mixed in a ratio of 1:100 to 1:

20.

6. The lignin janus hydrogel patch according to claim 5, characterized in that: In the preparation of the lignin mixed solution: the metal salt solution is any one of copper nitrate, aluminum nitrate, silver nitrate, zinc nitrate and iron nitrate, preferably, the concentration of the metal salt solution is 0.5 mg / mL to 5.5 mg / mL; the lignin is alkali lignin with a molecular weight of 500-10000 or sodium lignin sulfonate with a molecular weight of 100-8000, preferably, the concentration of the lignin solution is 0.1 mol / L-0.4 mol / L.

7. A method for preparing a lignin janus hydrogel patch, characterized in that: The following steps are included Preparation of the base layer: one side of the silica gel sheet is hydroxylated to obtain a modified base layer; Preparation of tissue adhesion layer solution: mixing ammonia water and aluminum nitrate solution, adding sodium lignin sulfonate to obtain a lignin aluminum / ammonia water mixed solution, mixing a monomer / gelatin mixed solution with the lignin aluminum / ammonia water mixed solution and adding at least one of acetone, β-keto acid, oxaloacetic acid, α-glutaric acid, phenylpropiotone or cyclohexanone to obtain a tissue adhesion layer solution, wherein the monomer is one or more of acrylic acid, acrylic acid and polyvinyl alcohol; Preparation of lignin janus hydrogel patch: stretching the modified base layer, coating the tissue adhesion layer solution on the hydroxylated surface of the modified base layer, and irradiating with ultraviolet light to polymerize the tissue adhesion layer solution in situ on the surface of the base layer.

8. The method for preparing the lignin janus hydrogel patch according to claim 7, characterized in that: The base layer is any one of a biological material, a composite material, and a polymer synthetic material, preferably silica gel; The other side of the substrate layer is fluorinated; preferably, the fluorinating agent is added dropwise and air-dried to fluorinate the silicone sheet; more preferably, the fluorinating agent is any one of trichloro(3,3,3-trifluoropropyl)silane, perfluorodecyltriethoxysilane and trimethoxy(3,3,3-trifluoropropyl)silane; The tissue adhesion layer solution is coated on the modified base layer and then air-dried after light irradiation.

9. Use of the lignin janus hydrogel patch according to any one of claims 1 to 6 in the preparation of a patch for promoting the healing of soft tissue defects or injuries.

10. The use according to claim 9; wherein: The patch for promoting the healing of soft tissue defects or injuries can initiate a strain program to perform mechanical self-contraction after contacting wet wound tissue; the soft tissue is visceral soft tissue or intestinal tissue; preferably, the intestinal wound is an infected intestinal wound.

Citation Information

Cited By

  • Self-adaptive super-contraction tendon adhesive with janus structure and preparation method of self-adaptive super-contraction tendon adhesive

    CN121534215A

  • A polyvinyl alcohol / sodium lignosulfonate-based conductive hydrogel and a preparation method thereof

    CN122541915A